2017
DOI: 10.1016/j.jped.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for candidemia mortality in hospitalized children

Abstract: Data from this study suggest that sepsis and septic shock, acute renal insufficiency, and risks like mechanical ventilation and dialysis are associated with increased mortality in pediatric patients. The mortality among patients with candidemia is high, and there is no species difference in mortality rates. Regarding the resistance rates, it is important to emphasize the presence of low resistance in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
3
4
1
4
Order By: Relevance
“…Also, we found that one Candida strain was resistant to FCY (2.3%). As azoles cross‐resistance is emerging nowadays our finding, in which 2 C. albicans strains resistant to ITR (2/10; 20%) were also resistant to other azoles (overall 4.6%) is in accordance to literature and to data from Europe (6.3%) and North America (6.6%) . Our strains were from adult settings and were not associated with mortality but it needs to be taken into consideration when planning azoles prophylaxis or therapy, especially in the Serbian NICU/PICUs.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Also, we found that one Candida strain was resistant to FCY (2.3%). As azoles cross‐resistance is emerging nowadays our finding, in which 2 C. albicans strains resistant to ITR (2/10; 20%) were also resistant to other azoles (overall 4.6%) is in accordance to literature and to data from Europe (6.3%) and North America (6.6%) . Our strains were from adult settings and were not associated with mortality but it needs to be taken into consideration when planning azoles prophylaxis or therapy, especially in the Serbian NICU/PICUs.…”
Section: Discussionsupporting
confidence: 86%
“…A national survey on risk factors associated with fungaemia and ICUs has not been done in Serbia yet, and this first hospital‐based report showed a majority of patients with proven Candida BSI, belonging to LBW neonates, patients with malignancy and abdominal surgeries, similar to data from the literature . A large portion of the Serbian ICU patients were severely ill, had vascular catheters or some medical devices, and were treated with broad spectrum antibacterial drugs.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…28 The detailed data are shown in Table 5. The annual incidence of neonatal IC was higher than that of non-neonatal IC in our study, which differs from results reported by Tragiannidis et al, 29 Motta et al, 30 Some previous reports showed that C albicans was the main species responsible for invasive Candida infection (C albicans > 50%). 20,25,31,33,34 Nevertheless, recent reports, including our study, have shown that non-albicans Candida species are becoming the dominant species responsible for invasive Candida infection.…”
Section: Among Neonates With Invasivecontrasting
confidence: 99%
“…The VRC resistance rate was higher than that reported by Tsai et al 37 and consistent with that in Sutcu et al's 31 report. The FCA resistance rates were lower than those reported by Ota et al 3 and Hsu et al, 28 higher than those reported by Santolaya et al, 19 Tsai et al 37 and Autmizguine et al, 33 and consistent with those reported by Tragiannidis et al, 18 Motta et al, 30 Sutcu et al 31 and Oncu et al 32 The 5-FC resistance rate was lower than that reported by Tragiannidis et al 18 and consistent with those reported by Tsai et al 37 and Sutcu et al 31 Susceptibility to AMB in this study was higher than that reported by Tragiannidis et al 18 and consistent with that reported by Tsai et al, 37 Motta et al, 30 Sutcu et al 31 and Autmizguine et al 33 The detailed data are shown in Table 2 and Table 7.…”
Section: Ta B L E 4 Factors Associated With 60-d Mortality By Multivasupporting
confidence: 82%